The Effect of Butter Addition and pH Treatment on Chemical Characteristic of Edible Gluten Film (Jurnal Ilmu dan Teknologi Hasil Ternak, 2008)
The purpose of this research to study the effect of the addition of butter and pH treatment on chemical characteristic of edible gluten film. The result showed that the addition of butter to edible gluten film gave a highly significant effect (P<0.01) on protein solubility, and gave a significant effect (P<0.05) on water content and lipid content, and didnot gave significant effect (P>0.05) on water activity. pH treatment gave a highly significant effect (P<0.01) on protein solubility and didnot gave significant (P>0.05) on water content, water activity and lipid content of edible gluten film. The interaction of addition of butter and pH treatment gave a highly significant effect (P<0.01) on protein solubility and give no significant (P>0.05) on water content, water activity and lipid content of edible gluten film. It could be concluded that the addition of butter and pH treatment decreased the water content and water activity, but increased lipid content and protein solubility. Â  Keywords : edible film, gluten, butter, pH